Diagnostic and statistical manual on mental disorders DSM-IV-TR. (American Psychiatric Association, 2000)
This text revision incorporates information culled from a comprehensive literature review of research about mental disorders published since DSM-IV was completed in 1994. Stay current with important updates to DSM-IV-TR. Benefit from new research into Schizophrenia, Asperger's Disorder, and other conditions. Utilize additional information about the epidemiology and other facets of DSM conditions. Updated information is included about the associated features, culture, age, and gender features, prevalence, course, and familial pattern of mental disorders. The DSM-IV-TR brings this essential diagnostic tool up-to-date, to promote effective diagnosis, treatment, and quality of care. Now you can get all the essential diagnostic information you rely on from the DSM-IV along with important updates not found in the 1994 edition.